Effect of supervised exercise training on objectively measured physical activity in patients during anthracycline therapyKey points - Caroline Schneider; Laura Stuetz; Annika Dierks; Kristin L. Campbell; Matthias Wilhelm; Prisca Eser (Elsevier, 2024)
Introduction: It is unknown what the benefits of cardio-oncologic rehabilitation programmes on cardiorespiratory fitness and cancer fatigue during anthracycline-based chemotherapies (AC) are with supervised exercise training (ET), compared to PA advice and tracking only. Methods: Patients with breast cancer or lymphoma were recruited from four cancer centres and randomly assigned to three months supervised ET during (EXduringAC) or after (EXpostAC) AC. All patients were counselled on physical activity (PA) and PA was objectively measured with an activity tracker. Primary endpoints were peak VO2, fatigue and quality of life (QoL) after AC (AC-end) and at follow-up (3 months after completion of AC). Secondary endpoints were daily PA and daily steps during AC and follow-up phase, which were compared between days with and without centre-based training sessions. All analyses were performed by linear mixed models. Results: Fifty-seven patients (median [1st and 3rd quartiles] age 47 years [38, 57 years]; 95 ​% women) consented to participate, of whom data from 51 patients were available. Despite the fact that PA on days with centre-based training sessions was 28 (95 ​% confidence interval 24-32) min higher with 4382 (3995-4768) more steps, neither PA nor steps differed between groups in neither AC nor follow-up phase, nor were there between group differences in peak VO2, QoL or fatigue at any time point. Conclusion: In physically active patients with cancer, PA advice and using an activity tracker was equally effective on changes in peak VO2, fatigue, or QoL as enrolling in centre-based ET performed during or after AC. Trial registration: NCT03850171, February 21, 2019.